2023
DOI: 10.1002/admi.202300504
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Size Control of Si Pyramid Texture for Perovskite/Si Tandem Solar Cells Enabling Solution‐Based Perovskite Top‐Cell Fabrication and Improved Si Bottom‐Cell Response

Yuqing Li,
Hitoshi Sai,
Calum McDonald
et al.

Abstract: A monolithic perovskite/silicon tandem solar cell architecture is employed to surpass the single‐junction efficiency limit. Recently, there is an increasing need for the double‐sided textures in the Si bottom cell to be compatible with the solution‐processed perovskite top cell from an industrial perspective. Herein, a silver‐assisted alkaline etching method is applied to fabricate nanoscale Si pyramid textures, and the influence of varying pyramid size (400–900 nm) on the interface morphology and the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The average absorption of the top cell in the UV-vis region increased up to 93.4%, with the active layer absorbing nearly 90% of the solar spectrum [83]. A monolithic perovskite/silicon tandem solar cell architecture has demonstrated the importance of double-sided textures in the Si bottom cell [84]. Varying pyramid size on Si surfaces has shown that reducing texture size to 400-500 nm results in high open-circuit voltage and enhanced bottom cell current due to suppressed reflectance, offering a route to increased tandem cell efficiency and reduced production costs [84].…”
Section: Green Energy Technologies: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The average absorption of the top cell in the UV-vis region increased up to 93.4%, with the active layer absorbing nearly 90% of the solar spectrum [83]. A monolithic perovskite/silicon tandem solar cell architecture has demonstrated the importance of double-sided textures in the Si bottom cell [84]. Varying pyramid size on Si surfaces has shown that reducing texture size to 400-500 nm results in high open-circuit voltage and enhanced bottom cell current due to suppressed reflectance, offering a route to increased tandem cell efficiency and reduced production costs [84].…”
Section: Green Energy Technologies: An Overviewmentioning
confidence: 99%
“…A monolithic perovskite/silicon tandem solar cell architecture has demonstrated the importance of double-sided textures in the Si bottom cell [84]. Varying pyramid size on Si surfaces has shown that reducing texture size to 400-500 nm results in high open-circuit voltage and enhanced bottom cell current due to suppressed reflectance, offering a route to increased tandem cell efficiency and reduced production costs [84]. The review of PSCs emphasizes the need for improved stability and efficiency via tandem configurations, addressing challenges against moisture, thermal, and UV light-induced degradation, particularly focusing on ZnO-based electron transport layers (ETL) [93].…”
Section: Green Energy Technologies: An Overviewmentioning
confidence: 99%